Abundance estimate, survival and site fidelity patterns of Blainville’s (Mesoplodon densirostris) and Cuvier’s (Ziphius cavirostris) beaked whales off El Hierro (Canary Islands) - Reyes Suárez, Crístel (University of St Andrews, 2018)
Beaked whales (Fam. Ziphiidae) comprise 22 different species, however due to their cryptic behaviour, information on these species is very limited. Beaked whales appear to be highly sensitive to anthropogenic noise, which can lead to mass strandings. The scarcity of knowledge about the abundance and population dynamics of most beaked whale species impedes the correct assessment of the effects that these impacts have on their populations. Coastal, year round populations of Blainville’s and Cuvier’s beaked whales were found in El Hierro (Canary Islands) in 2003. Long-term photo-ID studies have been conducted since then using a combination of land and at sea observations. Here I present the first results relating to site fidelity, abundance estimates and apparent survival for Blainville’s and Cuvier’s beaked whales in the Northeast Atlantic. The number of identifiable adults, i.e. animals with regular to very good photos and recognizable marks in the same area of the body, comprises 69 Blainville´s and 66 Cuvier´s beaked whales. Individuals that were captured in only one year are considered transients (T) while animals seen in multiple years are defined here as recaptured (R). Analysis of site fidelity patterns showed that 35% and 53% of the marked population on Blainville’s and Cuvier’s, respectively, were recaptured and form island-associated populations with a pattern of residence in the area. In Blainville’s, females spend longer periods in coastal waters than males and indeterminate whales (subadults or adult females never observed with calves). Males visit the area during shorter periods and there is an apparent hierarchy in individual male use of the area. Indeterminate individuals seem to emigrate after a 3 year period. These data coincide with results from Bahamas in showing a higher number of females than males with high site philopatry, and less philopatry in subadults. It has been proposed that these observations in Bahamas could be explained by males fighting for access to the female resident ...